Competencies of Chemistry Teachers and Prospective Teachers: A Literature Review - Alessandro Jeremi Manarisip; Rabiatul Adawiyah; Sri Handayani (Postgraduate, University of Mataram, 2023)
The role and function of teachers as professionals is to implement the national education system and realize national education goals, which is to develop the potential of students. Therefore, the competence and professional development of teachers must be in line with the way they carry out learning, especially in chemistry subjects. Where this subject is one of the subjects that most students are less interested in. The focus of this research is to collect information about the outcome of research that discusses the competence of chemistry teachers and prospective teachers, the research design uses a literature review with a qualitative descriptive approach. Reviewed 3 selected journals registered in Science and Technology Index (SINTA), and 17 SCOPUS indexed international journals. The collection of articles starts from 2016 to 2023. The most frequently used research type is qualitative with a case study research type, the most frequently used data collection instrument is observation with triangulation techniques. Chemistry teacher competencies needed at this time are PCK, CK, AK, PCK_CCC, TPASK, topic-specific PCK (TSPCK), argumentation, laboratory skill competence, technological knowledge, professional competence, and competence in organizing lesson study